Physicochemical changes in bone bioapatite during the late postmortem interval pre- and post-burning - Végh, EI; Márquez-Grant, N; Schulting, RJ (SAGE Publications, 2022)
Postmortem chemical transformation of bone bioapatite can take place during early diagenesis, resulting in a more thermodynamically stable mineral phase. This paper examines the impact of a one year postmortem interval on unburnt and burnt bone's structural and chemical alterations. This question is of importance for the reconstruction of funerary practices involving cremation in the archaeological record, as well as forensic anthropological investigations. Fleshed pig (Sus scrofa) tibiae were left exposed in a field, then collected at 14, 34, 91, 180, and 365 day intervals prior to being burnt in an outdoor fire (≤750 °C bone temperature). Fresh (fleshed) tibiae acted as unburnt and burnt controls. Also included in the study were two cremated human bone fragments from Middle-Late Neolithic (ca. 3300-2500 BCE) Ireland. Samples were analyzed for major and trace elements using an electron microprobe wavelength dispersive analyzer and molecular structures using Fourier transform infrared spectroscopy. Linear regression, principal component analysis, linear discriminant analysis, and multivariate analysis of variance were performed for statistical analysis. Results indicate that the concentrations of elements associated with extracellular fluid (K, Na, and Cl) change with the postmortem interval (PMI) and survive burning. K values under 0.07 ± 0.01 wt% in the inner and mid-cortical zones of burnt bones suggest that bones were not burnt immediately after death. Using this criterion, results from the archaeological samples would indicate a PMI of at least weeks to months prior to cremation. Ca, P, Fe, Al, Si, and Sr are not significantly altered with burning, and Fe, Al, Si, and Sr are also unaffected by the PMI. In unburnt bones increased crystallinity and carbonate loss are detectable in <1 year, but both are obscured by burning. Structurally, the carbonate to phosphate ratio (C/P), the phosphate high temperature, and cyanamide to phosphate (CN/P) are the most useful ratios for discriminating between unburnt and burnt bones.